Edukasi Risiko Baby Wrist Pada Ibu Balita di Posyandu Karangjati, Malang - Almardyah, Agashi Al'Ainaa; Oliviyan, Diva Amanda; Fitria, Cindy Dwi; Dhiyanisa, Nabila Randy; Humaira, Najah Fadiya; Dwiyaniti, Reni; Prastowo, Bayu; Istiyanisngsih, Sucik; Trianasari, Linda (Abdi Geomedisains, 2025)
Baby Wrist is a common condition that occurs in mothers around 8 months postpartum. It is a tenosivitis known as De Quervain Syndrome or injury to the dorsal compartment of the first wrist. The incidence of baby wrist is 6 times more common in women than men due to the use of the dominant hand during middle age. Early detection and prevention can restore movement function, physical limitations, and discomfort due to injury. This service aims to reduce the risk of baby wrist in mothers of toddlers at Posyandu Karangjati, Malang. The method used in this Community Service is Service Learning (SL). In general, participants complained of pain when carrying, breastfeeding, and doing daily activities. Finkelstein's Test is used as an early detection of baby wrist with the impression of pain on the radial side of the wrist to the thumb. The community service program was able to increase knowledge and understanding of baby wrist in participants. In addition, participants were able to demonstrate home exercise movements as a rehabilitative effort.